Combination therapy in overactive bladder‐untapped research opportunities: A systematic review of the literature. Issue 8 (4th September 2019) - Kasman, Alex; Stave, Christopher; Elliott, Christopher S.
Abstract: Aims: Overactive bladder (OAB) affects over 17% of the population and significantly effect the health‐related quality of life. The treatments for OAB include first line (lifestyle modification, pelvic floor muscle training), second line (anticholinergic or beta‐3 agonist medications), and third line therapies (intradetrusor botulinum toxin injection, sacral neurostimulation [SNM], or percutaneous tibial nerve stimulation [PTNS]). For those with urinary incontinence secondary to OAB, complete continence is the goal of therapy, though cure rates are only 5% to 40%. The use of combination therapies can be employed in refractory OAB, however, the efficacy of pooled modalities is relatively unknown. Our objective was to determine the volume of data supporting combination therapy in treating OAB. Methods: We systematically reviewed PubMed, EMBASE, the Cochrane Library, and Google Scholar for articles published before October 2018. Each was independently reviewed by two reviewers and examined in detail if they met inclusion criteria. Results: A total of 32 studies met inclusion criteria and were reviewed. Most large prospective studies evaluated combinations of medications with behavioral therapy or medications together. Combination therapy studies of third‐line treatments were rare and centered on medication with PTNS. No studies examined intradetrusor botulinum toxin injections in combination with another therapy and only one retrospective study briefly examined SNM therapy in combination with medication. Conclusion: Combination therapy, with certain first, second, and third‐line OAB therapies, appears to be efficacious. There is a further need for carefully designed combination therapy studies, particularly those including third line modalities.